2013
DOI: 10.1103/physrevlett.110.107201
|View full text |Cite
|
Sign up to set email alerts
|

Superspin Glass Mediated Giant Spontaneous Exchange Bias in a Nanocomposite ofBiFeO3Bi2Fe4O9

Abstract: We observe an enormous spontaneous exchange bias (~300-600 Oe)--measured in an unmagnetized state following zero-field cooling--in a nanocomposite of BiFeO(3) (~94%)-Bi(2)Fe(4)O(9) (~6%) over a temperature range 5-300 K. Depending on the path followed in tracing the hysteresis loop--positive (p) or negative (n)--as well as the maximum field applied, the exchange bias (H(E)) varies significantly with | - H(Ep) | > | H(En) |. The temperature dependence of H(E) is nonmonotonic. It increases, initially, till ~150 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
102
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 143 publications
(114 citation statements)
references
References 16 publications
8
102
1
3
Order By: Relevance
“…The coarser BiFeO 3 particles, on the other hand, are antiferromagnetic with uncompensated local spins. It has also been observed that there are superparamagnetic domains with a blocking temperature T B > 350 K. 4 The memory effect, on the other hand, signifies the presence of superspin glass moments. As the interparticle distance reduces and the exchange interaction increases, the superparamagnetic domains give way, initially, to superspin glass phase and then even superferromagnetic phase as well.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The coarser BiFeO 3 particles, on the other hand, are antiferromagnetic with uncompensated local spins. It has also been observed that there are superparamagnetic domains with a blocking temperature T B > 350 K. 4 The memory effect, on the other hand, signifies the presence of superspin glass moments. As the interparticle distance reduces and the exchange interaction increases, the superparamagnetic domains give way, initially, to superspin glass phase and then even superferromagnetic phase as well.…”
mentioning
confidence: 99%
“…In recent times, the spontaneous exchange bias (SEB) has been reported for different alloys and nanoparticle composite systems. [1][2][3][4] The origin of this appears to be lying in the biaxiality of AFM grains and variation in the FM-AFM bias coupling among an ensemble of grains. We report here that we have observed an even more interesting feature of the SEBvariation in the magnitude of the bias depending on the path followed in tracing the hysteresis loop-in a nanocomposite of BiFeO 3 -Bi 2 Fe 4 O 9 .…”
mentioning
confidence: 99%
See 3 more Smart Citations